An expert consensus on managing allergic cough in the pediatric set-up - Roy, Sitesh; Ganapathy, Sridhar; Mathur, Ashish; Chakarvarty, Ashok; Joshi, Devesh K.; Gala, Monil; Muchhala, Snehal S.; Kotak, Bhavesh P. (International Journal of Basic & Clinical Pharmacology, 2024)
Allergic cough frequently serves as a symptom of more comprehensive allergic conditions and is associated with a range of environmental and genetic factors. The presence of chronic conditions such as asthma, rhinitis, and sinusitis play a substantial role in the development of allergic cough in children. Allergic rhinitis affects up to 40% child population worldwide. Modified Delphi statements were prepared, and an agreement/disagreement was taken by12 expert paediatricians from India on these statements. The opinions of the expert panel were captured and documented. Consensus was predetermined to be obtained if more than 75% of the participants agreed (or remained neutral) on the statement. 12 pediatricians participated in the panel and provided opinions on 24 modified Delphi statements. All the statements were supported by the latest data from the literature search. 23 statements reached consensus after an agreement (agree + neutral) of more than 75%. In the event of non-agreement, 1 statement was amended as per the panel’s recommendation and sent for another round of deliberation. In the final phase, all the opinions from experts were consolidated and recommendations were framed. The present manuscript provides consensus recommendations for the pediatricians while addressing the allergic cough and related complications in the children. The key outline is to diagnose the proper cause of the cough and follow the proper treatment approach to avoid complications and have better management.